TANGGUNG JAWAB KURATOR PADA TENAGA KERJA YANG DI – PEMUTUSAN HUBUNGAN KERJA (PHK) AKIBAT DARI PERSEROAN TERBATAS YANG DINYATAKAN PAILIT - Eltarini Suksmananda, Ayu Putu; Markeling, I Ketut (Kertha Semaya : Journal Ilmu Hukum, 2014)
The background of this writing in a company bankruptcy caused thetermination of employment relationships (LAYOFFS) and of course give rise tobarriers to the Curators in the fulfillment of rights – the rights of workers. In the caseof a company that is experienced in bankruptcy, labor should have precedence ofpayment, wages of workers often occur unnoticed by Curators. The purpose of thiswriting is to know the responsibility of the curator on manpower in – LAYOFFS in alimited liability company that was declared bankrupt. So from that research will bediscussed regarding the barriers – barriers that will be faced by curators in takingcare of and deal with property in bankruptcy related to the wage labor is in – layoffsand the responsibility of the curator of the workforce at the company's bankrupt onLAYOFFS –. In this study the juridical normative research methods used to comparethe provisions of laws – an invitation to the Laws Number 37 of 2004 aboutbankruptcy and Suspension of payment with the Laws Number 13 Year 2013 aboutEmployment. Conclusion in this writing to know the barriers – barriers curator intaking care of and deal with property in bankruptcy and to determine theresponsibility of the curator of the workforce laid off at a limited liability companythat was declared bankrupt.
Keywords: Bankruptcy, Workers, Curator